Aplikasi Klinis DMSA Scan dalam Bidang Nefrourologi - Raden Erwin Affandi; William Korompis (Jurnal Health Sains, 2022)
DMSA (meso-2,3-dimercaptosuccinic acid) is a compound that contains a sulfhydryl group. This compound can chelate with various heavy metal compounds. At first, DMSA was used as heavy metal poisoning antidote, but with the development of science, nowadays DMSA has been successfully labelled with Tc-99m Pertechnetate and used in nuclear medicine examination. DMSA scan has been widely used in various nephrourology conditions, especially to detect kidney scar in urinary tract infection (UTI). DMSA scan can also be used to detect acute pyelonephritis, to detect ectopic kidney, to detect congenital kidney anomalies, and to measure relative kidney function. The purpose of this research was to depict various applications of DMSA scan in nephrourology field. This research is a study using the method of literature study or literature review. The conclusion of this research is DMSA scan can be a choice for clinician in day to day practice especially in detection of kidney scar in  UTI patient